An efficient polymer acceptor via a random polymerization strategy enables all-polymer solar cells with efficiency exceeding 17%. Issue 9 (21st July 2022) - Li, Yun; Li, Qian; Cai, Yunhao; Jin, Hui; Zhang, Jianqi; Tang, Zheng; Zhang, Chunfeng; Wei, Zhixiang; Sun, Yanming
Abstract : A series of polymer acceptors have been synthesized. The optical and electronic properties of the copolymers can be well-tuned via a random copolymerization strategy. The best-performing PY-82-based binary device produces a record-high efficiency of 17.15%. Abstract : The past few years have witnessed rapid progress of all-polymer solar cells (all-PSCs), however, the simultaneous achievement of high open-circuit voltage ( V oc ), short-circuit current density ( J sc ) and fill factor (FF) still remains a critical challenge. Herein, we used a random copolymerization strategy to develop a series of polymer acceptors named PY-X (where X stands for the molar ratio of two monomers) by polymerizing small molecule acceptor (SMA) monomers of SMA-C11 and SMA-DT with 2, 5-bis(trimethylstannyl)thiophene as the connecting unit. Upon random copolymerization, the optical and electronic properties of the polymer acceptors can be well tuned. Consequently, compared with PY-C11 and PY-DT, the random copolymer based all-PSCs exhibit improved PCEs. The best-performing device based on PY-82 produces a high PCE of 17.15% (certified as 16.7%), with a V oc of 0.950 V, a J sc of 23.82 mA cm −2, and an FF of 75.8%, representing the highest efficiency reported for the binary all-PSCs to date. This work suggests that random copolymerization is a promising synthetic strategy in developing efficient polymer acceptors.